Analysis of the Implementation of Love for the Motherland Character Education Through Civic Education Subjects at SD Negeri Karanggintung 01 Gandrungmangu Cilacap - Lutfi Cahyadi; Wakhudin Wakhudin (UM Purwokerto Press, 2023)
The purpose of this study is to find out how (1) Planning for Love of the Motherland Character Education through Civic Education Subjects at SD Negeri Karanggintung 01 Gandrungmangu Cilacap; (2) Implementation of Love for the Motherland Character Education through Civic Education Subjects at SD Negeri Karanggintung 01 Gandrungmangu Cilacap; (3) Analysis of the Implementation of Love for the Motherland Character Education through Civic Education Subjects at SD Negeri Karanggintung 01 Gandrungmangu Cilacap. This research uses a descriptive qualitative approach and with the chosen method, namely the case study method. Data collection techniques in this study used in-depth interviews, observations and document studies with interactive analysis. Based on the results of the study, it shows that (1) Education Planning for the character of love for the homeland through Civic Education subjects at SD Negeri Karanggintung 01 Gandrungmangu Cilacap was carried out with good planning. Before conducting character education, love for the teacher's homeland, educators prepare learning tools in the form of syllabi, lesson plans, assessment instruments and teaching materials. Then in learning media educators prepare laptops and LCD Projectors. Educators have an important task in teaching and learning activities in the classroom, therefore an interactive learning model with student character is needed. (2) The implementation of character education for love of the homeland through Civic Education subjects at SD Negeri Karanggintung 01 Gandrungmangu Cilacap uses learning models and learning media that are in accordance with the conditions of students so that students are enthusiastic about participating in teaching and learning activities and making learning goals easier to achieve. (3) Analysis of character education of love for the homeland through Civic Education subjects at SD Negeri Karanggintung 01 Gandrungmangu Cilacap found that character education can present positive traits for students regarding knowledge and the importance of meaning contained in civic education learning. The implementation of character education Love for the homeland has a significant influence on the formation of student character can be seen from the value of students above the minimum completeness criteria and in seen in activities that reflect the character of love for the homeland in flag ceremonies, picket squads and extracurricular activities.